The Effectiveness of Village Funds in Alleviating Rural Poverty: A Case Study of Belitung Regency - Asep Hariyanto; Bambang Juanda; Ernan Rustiadi; Sri Mulatsih (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Poverty is always synonymous with disadvantaged people in rural and urban areas. According to the OECD (2016) three billion people in developing countries, including Indonesia, live in rural areas, and the majority are poor. The government has made various efforts in Indonesia to alleviate poverty, including through the concept of